1977
DOI: 10.1093/jxb/28.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity, Carbon Dioxide Concentration, and Leaf Temperature on Gas Exchange of Spray Carnation Plants

Abstract: The rates of CO2 assimilation by potted spray carnation plants (cv. Cerise Royalette) were determined over a wide range of light intensities (45-450 W m~2 PAR), CO2 concentrations (200-3100 vpm), and leaf temperatures (5-35 °C). Assimilation rates varied with these factors in a way similar to the response of single leaves of other temperate crops, although the absolute values were lower. The optimal temperature for CO2 assimilation was between 5 and 10 °C at 45 W m~2 PAR but it increased progressively with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…Considering spe- cific differences between greenhouses (or growth chambers) and open fields, the environments in greenhouses generally have more (1) ideal temperature, (2) optimum humidity and soil moisture, (3) adequate nutrients, and ( 4) reduced solar radiation. With respect to temperature, the data probably adequately represent the field because photosynthesis responses to changing C0 2 concentration are not markedly different at different temperatures over a range at which the crops are normally grown (Gaastra, 1959;Enoch and Hurd, 1977). The more ideal moisture conditions in greenhouses also do not invalidate the data because the two C0 2 enrichment studies which included moisture stress as a variable showed that water-stressed wheat responded to C0 2 about as much or more than well-watered wheat (Gifford, l979a, l979b;Sionit et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering spe- cific differences between greenhouses (or growth chambers) and open fields, the environments in greenhouses generally have more (1) ideal temperature, (2) optimum humidity and soil moisture, (3) adequate nutrients, and ( 4) reduced solar radiation. With respect to temperature, the data probably adequately represent the field because photosynthesis responses to changing C0 2 concentration are not markedly different at different temperatures over a range at which the crops are normally grown (Gaastra, 1959;Enoch and Hurd, 1977). The more ideal moisture conditions in greenhouses also do not invalidate the data because the two C0 2 enrichment studies which included moisture stress as a variable showed that water-stressed wheat responded to C0 2 about as much or more than well-watered wheat (Gifford, l979a, l979b;Sionit et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to solar radiation, the data may also be biased, but in the direction opposite of that for nutrients. Photosynthesis and yield increase more with C0 2 enrichment at the higher light intensities characteristic of field conditions than at the lower intensities typical of greenhouses, particularly in winter (Gaastra, 1979;Enoch and Hurd, 1977;Kimball and Mitchell, 1979). Also, under the highest light intensities many of the greenhouses were not enriched, because ventilation was used for temperature control, in contrast to future fields which will have higher C0 2 concentrations continuously.…”
Section: Resultsmentioning
confidence: 99%
“…3A). As shown in carnation (Enoch & Hurd 1977) and rose (Jiao et al 1991), the optimum temperature for PR decreases as the light intensity decreases. The stems and bulb roots of plants grown under high DT of 28°C had a significantly low DW (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Normally net photosynthesis (Pn) increases with increasing CO2 concentrations up to a point of saturation where further increases in CO2 do not increase Pn. As CO2 concentration or irradiance increases, the optimum temperature for maximum Pn also increases (Gaastra, 1959;Enoch and Hurd, 1977). Wittwer and Robb (1964) recommended that greenhouse daytime temperature be elevated 3 to 5.5°C during CO2 enrichment.…”
Section: Photosynthesismentioning
confidence: 99%